MULTIPLE-INPUT SINGLE-OUTPUT VOLTAGE-MODE MULTIFUNCTION FILTER BASED ON VDDDAS - Huaihongthong, Pintira; Suwanjan, Peerawut; Siripongdee, Surapong; Jaikla, Winai; Chaichana, Amornchai (My University, 2023)
In recent years, the voltage differencing differential difference amplifier (VDDDA) has been used in various analog signal processing circuit designs. A second-order multifunction filter with multiple-inputs and single-output (MISO) voltage mode using VDDDA as active elements is proposed in this paper. The structure of the proposed filter comprises two VDDDAs, two grounded capacitors, and two resisters. The proposed filter has a cascadability feature in a voltage-mode sys-tem, producing voltage input and voltage output at high and low impedance ports, respectively. It can offer responses for all-pass (AP), band-reject (BR), band-pass (BP), low-pass (LP), and high-pass (HP) filters without additional inverting and double gain amplifiers, as well as the matching conditions. Choosing the appro-priate input signals provides these five filter responses in the same circuit topology. With two VDDDAs, the bias currents can be utilized to electronically tune the natural frequency (ω0) independently from the quality factor (Q). Experimental results using available com-mercial ICs have supported the theoretical expectations and confirmed the practical operation of the proposed multifunction biquad filter.
Keywords: AD830; electronical controllability; LM13700; MISO; Multifunction filter; VDDDA; voltage-mode circuit